Analysis of Software-Defined Networking Resilience to Link Failure through Failover Routing Simulation - Naharotul Istiqomah; Muhammad David Irsyadus Sholihin; Innasya' Putri Hidayati (Universitas Islam Raden Rahmat, Malang, 2026)
Software-Defined Networking (SDN) represents an advanced architectural paradigm that separates control logic from data forwarding, enabling centralized and adaptive network management. This study investigates SDN resilience under link failure conditions and evaluates the effectiveness of failover routing in restoring network performance. Simulation-based experiments are conducted on a redundant logical topology implemented using Python and the NetworkX library, covering three operational phases: normal operation, link failure, and failover recovery. The results show that link failures cause a noticeable degradation in network performance, with normalized link utilization increasing due to traffic concentration on limited paths. After failover routing is activated, network performance improves significantly, achieving up to approximately 15–20% higher normalized link utilization compared to the failure state, indicating successful traffic rerouting and service restoration. These findings demonstrate that failover routing enables rapid recovery and maintains service continuity despite link disruptions. This study contributes to SDN resilience research by providing a reproducible logical-topology simulation framework and quantitative evidence that proactive, controller-based failover routing effectively enhances network robustness under link-failure scenarios, offering practical insights for resilient SDN design in data center and enterprise environments.